STRATEGI KEUANGAN DAN PERTUMBUHAN: DAMPAK STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Fitri Noviera; Christina Dwi Astuti; Oktaviani, Ayu Aulia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Firm’s value is an important indicator that reflects the company's performance and future prospects. Determining firm’s value is influenced by various factors, including capital structure, profitability, and company size. This research focuses on the basic materials sector, which plays an important role in the economy and often faces the challenges of price and demand volatility. In the 2021-2022 period, this sector faces various dynamics that affect firm value. By using purposive sampling methods and multiple regression analysis, this research aims to identify the influence of capital structure, profitability and company size on firm value in the basic materials sector. The main finding of this research is that capital structure has a significant effect on firm value, while profitability and company size do not have a significant effect. These results contribute to understanding the relationship between financial factors and firm value in the basic materials sector. The implication of these findings is that investors can consider capital structure as a factor in making investment decisions, while company management needs to pay attention to capital structure management, profitability and company size to avoid a decline in firm value.